P94 Cardiorespiratory physiology in patients with copd according to blood eosinophilia: data from the erica cohort. (15th November 2017) - Buss, L; McKeever, TM; Mohan, D; Maki-Petaja, K; Forman, J; McEniery, CM; Cheryian, J; Gale, N; Cockcroft, JR; Calverley, PM; MacNee, W; Tal-Singer, R; et al.
Abstract : Introduction: Blood eosinophils level in Chronic Obstructive Pulmonary Disease (COPD) is a candidate biomarker for Regulatory qualification as a drug development tool identifying individuals who may benefit from targeted therapies. Current evidence focused on association with exacerbations and response to therapy, however the association of eosinophilia with cardiorespiratory physiology has not been determined. Methods: The ERICA (Evaluating the Role of Inflammation in Chronic Airway Disease) study is a large multicentre study of patients with COPD. 1 Aortic pulse wave velocity (PWV), carotid intimal thickness (CIMT) and spirometry were measured. Health Status (CAT) was recorded. From the full blood count, both absolute and percentage eosinophil counts were considered. We used previously validated cut offs 2 of 0.3 × 10 9 cells/L and 2% to compare aortic PWV, CIMT and spirometry variables using a Student's t-test. A multivariate model was then built to examine the effect after adjusting for confounding factors. Results: 519 subjects were included in this analysis. Of these, 58% were men, mean (SD) age of 66.9 (7.6) years with a median smoking history of 42 pack years. Mean (SD) resting heart rate was 75 (13)bpm, mean arterial pressure 104 (12) mmHg and percentage predicted FEV1 52.5 (16.1)%. When comparing high and low eosinophil groups at both 0.3 × 10 9 cells/L and 2% cut-offs there was no difference in smoking status or pack years, spirometry variables or CAT score. There was no difference in prevalence of ischaemic heart disease, stroke or diabetes. Aortic PWV or CIMT were not different between groups. Multiple regression confirmed this (Table ). Conclusions: A phenotype defined by blood eosinophilia does not relate to cardiorespiratory physiological variables in subjects with COPD. References: Mohan Det al. Journal of COPD 2015. Negewo Net al. Respirology2017.